Air pollution and childhood asthma. Issue 2 (24th April 2023) - Mukharesh, Lana; Phipatanakul, Wanda; Gaffin, Jonathan M.
Abstract : Purpose of review: Asthma is the most common chronic disease of childhood. Environmental exposures, such as allergens and pollutants, are ubiquitous factors associated with asthma development and asthma morbidity. In this review, we highlight the most recent studies relevant to childhood asthma risk, onset, and exacerbation related to air pollution exposure. Recent findings: In this article, we review current research that has been published between 2021 and 2022, demonstrating the effects of early-life exposure to key air pollutants (e.g., particulate matter (PM), nitrogen dioxide (NO2 ), sulfur dioxide (SO2 ) and ground-level ozone (O3 ), environmental tobacco smoke, radon, and volatile organic compounds (VOC) on respiratory health. Summary: Air pollution continues to be a global burden with serious consequences related to respiratory health. Interventions aimed at reducing air pollution in the environment must be achieved in an effort to improve asthma outcomes and pediatric health.